Determinan return saham pada perusahaan sektor barang konsumsi di Bursa Efek Indonesia: Peran mediasi profitabilitas - Lyvania Unbanunaek; Maria Asumpta Evi Marlina (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2026)
This study examines the determinants of stock returns in the Consumer Non-Cyclicals sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period, with profitability, proxied by Return on Assets (ROA), serving as a mediating variable. A quantitative research approach was employed using panel data consisting of 355 firm-year observations from 71 companies. The data were analyzed using the Ordinary Least Squares (OLS) regression method and the Sobel test to examine the mediating effect of profitability. The results indicate that liquidity has a positive and significant effect on profitability, whereas asset allocation efficiency does not significantly affect profitability. Furthermore, profitability fully mediates the relationship between liquidity and stock returns but fails to mediate the effect of asset allocation efficiency on stock returns. In addition, Leverage negatively affects profitability, while Firm Size has a positive effect on profitability; however, neither variable exerts a direct influence on stock returns. These findings highlight the critical role of profitability as a transmission mechanism linking liquidity to stock returns, suggesting that investors should place greater emphasis on a firm's ability to generate profits rather than relying solely on liquidity information when making investment decisions.